Stability of Structured Kaposi's Sarcoma-Associated Herpesvirus ORF57 Protein Is Regulated by Protein Phosphorylation and Homodimerization - Majerciak, Vladimir (J Virol, 2015)
Kaposi's sarcoma-associated herpesvirus (KSHV) ORF57 plays an essential role in KSHV lytic infection by promoting viral gene expression at the posttranscriptional level. Using bioinformatic and biochemical approaches, we determined that ORF57 contains two structurally and functionally distinct domains: a disordered nonstructural N-terminal domain (amino acids [aa] 1 to 152) and a structured α-helix-rich C-terminal domain (aa 153 to 455). The N-terminal domain mediates ORF57 interaction with several RNA-protein complexes essential for ORF57 to function. The N-terminal phosphorylation by cellular casein kinase II (CKII) at S21, T32, and S43, and other cellular kinases at S95 and S97 residues in proximity of the caspase-7 cleavage site, 30-DETD-33, inhibits caspase-7 digestion of ORF57. The structured C-terminal domain mediates homodimerization of ORF57, and the critical region for this function was mapped carefully to α-helices 7 to 9. Introduction of point mutations into α-helix 7 at ORF57 aa 280 to 299, a region highly conserved among ORF57 homologues from other herpesviruses, inhibited ORF57 homodimerization and led to proteasome-mediated degradation of ORF57 protein. Thus, homodimerization of ORF57 via its C terminus prevents ORF57 from degrading and allows two structure-free N termini of the dimerized ORF57 to work coordinately for host factor interactions, leading to productive KSHV lytic infection and pathogenesis. IMPORTANCE KSHV is a human oncogenic virus linked to the development of several malignancies. KSHV-mediated oncogenesis requires both latent and lytic infection. The KSHV ORF57 protein is essential for KSHV lytic replication, as it regulates the expression of viral lytic genes at the posttranscriptional level. This report provides evidence that the structural conformation of the ORF57 protein plays a critical role in regulation of ORF57 stability. Phosphorylation by CKII on the identified serine/threonine residues at the N-terminal unstructured domain of ORF57 prevents its digestion by caspase-7. The C-terminal domain of ORF57, which is rich in α-helices, contributes to homodimerization of ORF57 to prevent proteasome-mediated protein degradation. Elucidation of the ORF57 structure not only enables us to better understand ORF57 stability and functions but also provides an important tool for us to modulate ORF57's activity with the aim to inhibit KSHV lytic replication.